Comparative advantages and cross-border mergers and acquisitions: the case of Chinese M&As in European countries. (2018) - Lepori, Damiano; Gugler, Philippe
The purpose of this study is to scrutinise the links between Chinese cross-border mergers and acquisitions (M&As) and of the export competitiveness of Chinese and of targeted countries' industries in which investors are competing. We base our study on the revealed comparative advantages (RCA) of both Chinese exports and recipient countries' exports. We develop hypotheses about the level of RCA of China in industries in which the corresponding M&As occur and the level of RCA of the recipient countries. We test our hypotheses on a sample composed of Chinese M&As realised in the eight main recipient countries registered from 2006-2016 in Europe. With respect to low-cost products, Chinese acquiring firms compete in industries with a high domestic RCA, whereas European target firms compete in industries with a high domestic RCA. With respect to more sophisticated products, Chinese acquiring firms compete in industries with a low domestic RCA and European target firms compete in industries with a high domestic RCA. Our study suggests the predominance of market-seeking investments in the first case and strategic asset-seeking investments in the second case.